Radical : Italian design 1965-1985 : the Dennis Freedman collection - Celant, Germano; Strauss, Cindi; Museum of Fine Arts, Houston (New Haven : Yale University Press ; [Houston] : in association with The Museum of Fine Arts, Houston, 2020)
"Radical: Italian Design 1965-1985, the Dennis Freedman Collection Examines Italian Radical design, including the movement's political and social roots and challenge to Modernism, from 1965 to 1985 through nearly 70 objects and architectural models, seven interviews with Radical designers and architects, and an essay by Germano Celant, the acclaimed author and curator who coined the term "Radical design.""--
Foreword / by Gary Tinterow -- Acknowledgments / by Cindi Strauss -- Interview with Dennis Freedman -- Introduction / by Cindi Strauss -- Italian Design : From Pop to Radical / by Germano Celant -- Italian Radical Design in the United States : Exposure, Availability, and Legacy / by Cindi Strauss -- Interview with Franco and Nanà Audrito, Studio65 -- Interview with Lapo Binazzi, UFO -- Interview with Andrea Branzi -- Interview with Alessandro Guerriero -- Interview with Ugo La Pietra -- Interview with Alessandro Mendini -- Interview with Franco Raggi.
"This book accompanies the exhibition Radical: Italian Design 1965-1985, The Dennis Freedman Collection, presented at the Museum of Fine Arts, Houston, February 9 through April 26, 2020."
Includes bibliographical references and index.
Keywords: Design -- Italy -- History -- 20th century -- Exhibitions; Radical architecture -- Italy -- Exhibitions